Implementasi Program Badan Usaha Milik Desa (BUMDes) Di Desa Polohungo Kecamatan Dulupi Kabupaten Boalemo - Noval Adriyanus Karim; Rosman Ilato; Raflin Hinelo (Universitas Negeri Gorontalo, 2020)
Abstract The research objective is to understand the determinant factor of Village-Owned Enterprises (BUMDes) Program in Polohungo Village. Dulupi Sub-district. Boalemo District. Method applied in this research is qualitative, while the analysis uses interview analysis. The research finding concludes that in general, the implementation of Village-Owned Enterprises (BUMDes) Program in Polohungo Village is well-performad as main program in the BUMDes like kopiah karanji (men’s typical cap made of rattan or dried water hyacinth) craft and the brick production show continuity. However the program has not run optimally as several matters require attention and improvement.